A influência de Heinrich Isaac em Anton Webern - Pereira, Maria Clara Peinado [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The present work consists of documenting evidence of the music influence and technique of the fifteenth and sixteenth century composer Heinrich Isaac on Anton Webern's music through musical analysis of Isaac's Choralis Constantinus and some of Webern's significant works.

O presente trabalho consiste na documentação de indícios da influência da música e técnica do compositor do século XV e XVI Heinrich Isaac na música de Anton Webern, por meio de análises musicais da obra Choralis Constantinus de Isaac e de algumas obras significativas de Webern.
Keywords: Isaac, Heinrich, 1450-1517; Webern, Anton, 1883-1945; Música - Análise, apreciação; Música - Séc. XVI; Música - Séc. XV; Music - 16th century